Leituron-line : compreensão de notícias no ciberespaço - Santana, Maria José Barreto de (2021)
The multiple languages which exist in cyberspaces require readers new skills in order to understand hypertexts. In this sense, the aim of this thesis is to develop a pedagogical proposal to work the reading of news in cybernetic environments. Therefore, we sought to understand how information processing occurs and to verify the cognitive and metacognitive reading strategies adopted by the students to reach the understanding of electronic texts. This study is justified by the need to teach students to read texts on screen, since this process does not occur in a natural way, as well as by the relevance of creating digital learning environments to develop reading practices, since the moment implies the coexistence of the culture of the printed and the digital culture. The methodology adopted is configured as a quantitative and qualitative approach of interventional nature of action research. The theoretical basis is constituted in the light of studies by authors such as Smith (1989), Santaella (2004), Xavier (2010), Araújo (2010), Marcuschi (2010), Coscarelli (2017), Moreira (2019), among others. Therefore, an interventional proposal was created to develop the comprehension of texts in digital environments. As a final product a website was elaborated, "Leituronline", containing all the activities proposed by this thesis. We expect to contribute to the reading training of students, so that they develop the skills to read hypertexts, thus becoming digital literate. We also intend to awaken in teachers the interest to teach students strategies to read texts in digital environments, in order to make Portuguese Language classes, especially those destined to readings of texts, less boring and more significant.